Thick electrode and preparation method and application thereof
By introducing modified nanocellulose into the electrode slurry and freeze-drying it, the problems of longer lithium ion transmission paths and poor pole piece performance in thick electrodes are solved, achieving higher mechanical strength and battery performance.
Patent Information
- Application Number
- CN202411517928.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, when preparing thick electrodes, there are problems such as lengthening of lithium ion transport path, slow reaction kinetics, increased electrode surface density, increased thickness, and deterioration of magnification and cycling performance.
By introducing modified nano -cellulose into the electrode slurry, freezing and drying, the flexible support structure is established, the mechanical strength of the polar sheet is improved, and the collapse and structural damage are prevented.
It effectively avoids pole piece collapse and improves battery performance, especially at high rates, improving the battery's cycle performance and energy density.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a thick electrode and a preparation method and application thereof. Background Art
[0002] As competition in the new energy industry becomes increasingly fierce, improving energy and reducing costs is one of the powerful ways to cope with market competition. Increasing the active material loading of the pole piece can not only reduce the use of inactive substances and reduce costs, but also increase energy density. However, as the active material loading of the pole piece increases, the pole piece surface density increases and the thickness also increases, which means that the transmission path of lithium ions becomes longer and the reaction kinetics slows down. Especially at higher rates, the battery polarization increases dramatically, resulting in poor rate and cycle performance.
[0003] In the prior art, patent application CN202410076099.7 discloses a method for preparing a thick electrode pole piece, which includes improvements in materials and processes. The porosity and tortuosity are controlled by coating two layers of slurry containing different types of binders and particle sizes of the main material, and the tortuosity of the upper layer is ensured to be less than that of the lower layer, thereby improving the electrochemical performance. However, the above technical solution has the following two disadvantages: First, in terms of materials: the binder is highly correlated with the processing of the electrode segment. At present, there are few products that can replace imported PVDF in the field of thick electrodes. If the binder is replaced to control the tortuosity, the effect is limited and the risk is relatively high; and the main materials of different particle sizes will affect the tortuosity of the pole piece. Considering that the selection of the main material needs to be selected according to the needs of the system, the consideration point is not only the particle size, so there are certain limitations in using the particle size to control the tortuosity. Secondly, in terms of process: in terms of preparation technology, the current method for reducing the tortuosity of the pole piece is mainly pore formation, including pore forming agent, template method, physical method, low vacuum filtration, water bath reverse phase transformation and other methods. Although these methods have certain effects, they are difficult to achieve large-scale production. Summary of the invention
[0004] In order to solve the above problems in the prior art, the present invention provides a ferric phosphate wastewater treatment system and a treatment method, so as to achieve stable operation of ferric phosphate wastewater treatment.
[0005] Based on this, the present invention has the following technical solutions: In a first aspect, the present invention provides a method for preparing a thick electrode, comprising: S1: mixing modified nanocellulose, a conductive agent, an electrode active material and a solvent to obtain a mixed slurry; wherein the content of carboxyl groups in the modified nanocellulose is 1.8-2.2 mmol / g; S2: freeze-drying the mixed slurry.
[0006] According to the method for preparing the thick electrode provided by the present invention, the modified nanocellulose is obtained by oxidizing the primary alcohol and / or secondary alcohol on the nanocellulose into a carbonyl group.
[0007] According to the preparation method of the thick electrode provided by the present invention, the preparation method of the modified nanocellulose comprises: mixing cellulose, TEMPO, sodium bromide and water, adjusting the pH to 9.8-10.2, adding sodium hypochlorite, and performing an oxidation reaction at room temperature and an ultrasonic frequency of 100-150 kHz, and after the reaction is completed, washing with water and filtering to obtain the modified nanocellulose.
[0008] According to the method for preparing the thick electrode provided by the present invention, in the mixed slurry, the amount of the modified nanocellulose is 1.1wt%~1.5wt%.
[0009] According to the method for preparing the thick electrode provided by the present invention, the mixed slurry comprises the following components in parts by weight: 1.1-1.5 parts of the modified nanocellulose; Conductive agent 0.5~1 part; 52.5-58.4 parts of electrode active material; 40~45 parts of solvent.
[0010] According to the method for preparing the thick electrode provided by the present invention, the conductive agent includes one or more of carbon black, acetylene black, carbon nanotubes, and graphene.
[0011] According to the preparation method of the thick electrode provided by the present invention, the electrode active material includes a sodium electroactive substance or a lithium electroactive substance, and the sodium electroactive substance includes: one or more of sodium vanadium phosphate, sodium vanadium manganese phosphate, sodium vanadium iron phosphate, sodium iron phosphate, sodium fluorophosphate, Prussian blue analogues, sodium cobaltate, sodium manganate, sodium nickelate and sodium ferrate; the lithium electroactive substance includes one or more of lithium iron phosphate, lithium manganese iron phosphate, lithium cobaltate, lithium nickelate and lithium manganate.
[0012] According to the method for preparing the thick electrode provided by the present invention, the solvent includes water.
[0013] According to the preparation method of the thick electrode provided by the present invention, the mixed slurry is first frozen at -70 to -30 degrees Celsius for 24 to 30 hours, and then freeze-dried at -70 to -50 degrees Celsius and 1.6 to 2.0 Pa for 24 to 48 hours.
[0014] In a second aspect, the present invention provides a thick electrode, which is prepared by the above-mentioned preparation method.
[0015] According to the thick electrode provided by the present invention, the porosity of the thick electrode is 40% to 45%.
[0016] In a third aspect, the present invention provides a battery, characterized in that it comprises the thick electrode.
[0017] The thick electrode and its preparation method and application provided by the present invention, by introducing the modified nanocellulose into the electrode slurry, establishes a flexible support structure in the electrode structure, which can not only effectively avoid collapse but also improve battery performance. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] In the prior art, pore-forming agents are mostly used to make holes in the pole pieces to increase the porosity of the pole pieces, thereby shortening the lithium ion transmission path; however, when using pore-forming agents to make holes in the pole pieces, the pore structure of the pole pieces is prone to collapse during the rolling stage, affecting the improvement effect. Alternatively, physical methods are used to directly transform the pole pieces into through holes, but when physical methods are used, such as using lasers to make holes in the pole pieces, the heat-affected zone will cause the active material to fail, affecting the battery capacity. Therefore, in the prior art, when preparing thick electrodes, there are problems such as the lengthened lithium ion transmission of thick electrodes and the poor processing performance of thick pole pieces, which are prone to cracking. There is room for further improvement in battery performance.
[0020] The present invention finds that by introducing the modified nanocellulose into the electrode slurry, due to its high electronegativity, the conductive carbon black and active materials will be adsorbed on the cellulose surface in the aqueous solution, and it will be shaped by freeze drying, thereby establishing a flexible support structure in the electrode structure, which can not only effectively avoid collapse but also improve battery performance.
[0021] Based on this, the present invention has the following technical solutions: In a first aspect, the present invention provides a method for preparing a thick electrode, comprising: S1: Mixing modified nanocellulose, a conductive agent, an electrode active material and a solvent to obtain a mixed slurry; wherein the content of carboxyl groups in the modified nanocellulose is 1.8-2.2 mmol / g.
[0022] S2: freeze-drying the mixed slurry.
[0023] The present invention finds that by modifying nanocellulose and controlling the content of carboxyl groups in the modified nanocellulose to be within the above range, the modified nanocellulose can be made to have abundant negative charges, and electrode active materials and conductive agents can be electrostatically adsorbed on the modified nanocellulose. In addition, the porous flexible supporting structure and excellent mechanical properties of the modified nanocellulose enable it to have good bonding with the electrode active materials and conductive agents; at the same time, it can effectively improve the mechanical strength of the electrode piece and prevent the electrode piece from cracking and structural collapse.
[0024] According to a preferred embodiment provided by the present invention, the modified nanocellulose is obtained by oxidizing the primary alcohol and / or secondary alcohol on the nanocellulose into carbonyl groups; specifically, the content of carboxyl groups in the modified nanocellulose can be 1.8 mmol / g, 1.9 mmol / g, 2.0 mmol / g, 2.1 mmol / g or 2.2 mmol / g, etc.
[0025] According to a preferred embodiment provided by the present invention, the preparation method of the modified nanocellulose comprises: mixing cellulose, TEMPO, sodium bromide and water, adjusting the pH to 9.8-10.2, adding sodium hypochlorite, and conducting an oxidation reaction at room temperature and an ultrasonic frequency of 100-150 kHz, and after the reaction is completed, washing with water and filtering to obtain the modified nanocellulose.
[0026] Further preferably, the preparation method of the modified nanocellulose comprises: mixing cellulose, TEMPO, sodium bromide and water, adjusting the pH to 9.8-10.2, adding 3-6 mmol / g sodium hypochlorite solution, and then carrying out oxidation reaction at room temperature and an ultrasonic frequency of 100-150 kHz, reacting for 6-10 hours, washing with water and filtering to obtain the modified nanocellulose.
[0027] In the present invention, the carboxyl content of the modified nanocellulose is related to the dosage of sodium hypochlorite and the stirring method. Within a certain range, the higher the dosage of sodium hypochlorite, the higher the carboxyl content in the obtained modified nanocellulose; at the same time, it is more conducive to controlling the carboxyl content under ultrasonic conditions.
[0028] According to a preferred embodiment provided by the present invention, in the mixed slurry, the amount of the modified nanocellulose is 1.1wt%~1.5wt%; for example, it can be 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%.
[0029] According to a preferred embodiment provided by the present invention, the mixed slurry comprises the following components in parts by weight: 1.1-1.5 parts of the modified nanocellulose; Conductive agent 0.5~1 part; 52.5-58.4 parts of electrode active material; 40~45 parts of solvent.
[0030] According to a preferred embodiment provided by the present invention, the conductive agent includes one or more of carbon black, acetylene black, carbon nanotubes, and graphene.
[0031] According to a preferred embodiment provided by the present invention, the electrode active material includes a sodium electroactive substance or a lithium electroactive substance, and the sodium electroactive substance includes: one or more of sodium vanadium phosphate, sodium vanadium manganese phosphate, sodium vanadium iron phosphate, sodium iron phosphate, sodium fluorophosphate, Prussian blue analogues, sodium cobaltate, sodium manganate, sodium nickelate and sodium ferrate; the lithium electroactive substance includes one or more of lithium iron phosphate, lithium manganese iron phosphate, lithium cobaltate, lithium nickelate and lithium manganate.
[0032] According to a preferred embodiment provided by the present invention, the solvent includes water.
[0033] According to a preferred embodiment provided by the present invention, the freeze-drying conditions include: first freezing the mixed slurry at -70 to -30 degrees Celsius for 24 to 30 hours, and then freeze-drying it at -70 to -50 degrees Celsius and 1.6 to 2.0 Pa for 24 to 48 hours.
[0034] The present invention finds that freeze-drying the mixed slurry containing the modified nanocellulose under the above freeze-drying conditions can further improve battery performance compared with conventional freeze-drying conditions.
[0035] In a second aspect, the present invention provides a thick electrode, characterized in that it is prepared by the above-mentioned preparation method.
[0036] According to a preferred embodiment provided by the present invention, the porosity of the thick electrode is 40%-45%.
[0037] In a third aspect, the present invention provides a battery comprising the thick electrode.
[0038] In order to further illustrate the thick electrode of the present invention, the present invention further provides the following examples and comparative examples.
[0039] Unless otherwise specified, the various raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.
[0040] Example 1
[0041] This embodiment provides a thick electrode, and the preparation method thereof comprises the following steps: S1: mixing modified nanocellulose, carbon black, lithium iron phosphate and water in a mass ratio of 1.3:0.75:55.95:42 to obtain a mixed slurry; S2: freeze-drying the mixed slurry, wherein the freeze-drying conditions include first freezing the mixed slurry at -30 degrees Celsius for 28 hours, and then freeze-drying it at 1.8 Pa and -50 degrees Celsius for 36 hours.
[0042] The preparation method of the modified nanocellulose comprises the following steps: 1 g of cellulose was suspended in water (100 ml) containing TEMPO (0.016 g, 0.1 mmol / g) and sodium bromide (0.1 g, 1 mmol / g), hydrochloric acid was added to adjust the solution pH to 10, NaClO solution (5 mmol / g) was added, and oxidation reaction was carried out at room temperature and an ultrasonic frequency of 150 kHz, while NaOH was added to maintain the solution pH at 10. After reacting for 10 hours, the modified nanocellulose was obtained by washing with water and filtering; the carboxyl content of the modified nanocellulose in this embodiment was 1.9 mmol / g.
[0043] Example 2
[0044] This embodiment provides a thick electrode, and the preparation method thereof is different from that of Embodiment 1 only in that: in the mixed slurry, the content of the modified nanocellulose is 1.1 wt %.
[0045] Example 3
[0046] This embodiment provides a thick electrode, and the preparation method thereof is different from that of Embodiment 1 only in that the content of the modified nanocellulose is 0.8 wt %.
[0047] Example 4
[0048] This embodiment provides a thick electrode, and its preparation method is different from that of Embodiment 1 only in that: the freeze-drying conditions include: first freezing the mixed slurry at -20 degrees Celsius for 24 hours, and then freeze-drying it at 1.8 Pa and -40 degrees Celsius for 24 hours, and the freeze-drying temperature.
[0049] Comparative Example 1
[0050] This comparative example provides a thick electrode, and the preparation method thereof is different from that of Example 1 only in that the modified nanocellulose described in Example 1 is replaced by modified nanocellulose prepared by the following method.
[0051] The carboxyl content of the modified nanocellulose in this embodiment is reduced to 1.4 mmol / g, and the preparation method thereof comprises the following steps: 1 g of cellulose was suspended in water (100 ml) containing TEMPO (0.016 g, 0.1 mmol / g) and sodium bromide (0.1 g, 1 mmol / g). Hydrochloric acid was added to adjust the solution pH to 10. NaClO solution (1.5 mmol / g) was added and reacted at room temperature and a stirring speed of 550 r / min. NaOH was added to maintain the solution pH at 10. After the reaction, the modified nanocellulose was washed with water and filtered.
[0052] Test example
[0053] The present invention tests the tortuosity and liquid phase diffusion impedance of the thick electrodes provided in the above embodiments and comparative examples. The test results are shown in Table 1.
[0054] Test method: Tortuosity Calculation logic:
[0055] Pole porosity ε = (pole volume - mass of each material / true density) / pole volume
[0056] Liquid phase diffusion impedance Rion is calculated by taking the unformed battery and the positive electrode sheet with 0% SOC to make a monolithic symmetrical battery. The EIS is tested with an electrochemical workstation and Rion is obtained by data processing.
[0057] Energy efficiency test method: 1. Place the test sample in the environmental simulator and connect it to the charging and discharging device; 2. Set the temperature of the environmental simulation device to 25 degrees Celsius; 3. Stand at (25±2) degrees Celsius for 5 hours; 4. Charge at a constant power of 0.5P until the battery monomer charging cut-off condition is reached, let stand for 10 minutes, and record the power, time, voltage, temperature, and charging energy; 5. Discharge at a constant power of 0.5P until the battery monomer discharge cut-off condition is reached, let stand for 10 minutes, and record the power, time, voltage, temperature, and discharge energy; 6. Initialization discharge is completed; 7. Charge at a constant power of 0.5P until the battery monomer charging cut-off condition is reached, let stand for 10 minutes, and record the power, time, voltage, temperature, and charging energy; 8. Discharge at a constant power of 0.5P to the battery monomer discharge cut-off condition, let it stand for 10 minutes, and record the power, time, voltage, temperature, and discharge energy; 9. Disconnect the test sample from the charging and discharging device, remove the data sampling line, and take out the test sample; 10. Divide the discharge energy in step 8 by the charge energy in step 7 to obtain the 0.5P charge and discharge energy efficiency of the test sample.
[0058] Cohesion test method: The pressure-sensitive tape is bonded to the stainless steel plate, and then the electrode is bonded to the pressure-sensitive tape, and then a layer of green glue is bonded to the electrode. The tensile testing machine clamps the green glue and peels it 180 degrees. The data of the tensile testing machine is read to obtain the cohesive force between the electrode materials.
[0059] Table 1
[0060] According to Table 1, the results show that compared with Examples 1-2, Example 3 has a lower content of modified nanocellulose, its tortuosity and liquid phase diffusion impedance are relatively high, and the energy efficiency and cohesion of the battery cell are relatively low; and compared with Examples 1-3, Example 4 uses conventional freeze-drying conditions to mix the slurry for freeze-drying, which will affect the battery effect to a certain extent. Compared with Examples 1-4, although Comparative Example 1 also modifies the nanocellulose, the carboxyl content of the modified nanocellulose is reduced to 1.4 mmol / g, which will significantly affect the effect.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a thick electrode, characterized in that: include: S1: mixing modified nanocellulose, a conductive agent, an electrode active material and a solvent to obtain a mixed slurry; wherein the content of carboxyl groups in the modified nanocellulose is 1.8-2.2 mmol / g; S2: freeze-drying the mixed slurry.
2. The method for preparing a thick electrode according to claim 1, characterized in that: The modified nanocellulose is obtained by oxidizing the primary alcohol and / or secondary alcohol on the nanocellulose into carbonyl groups.
3. The method for preparing a thick electrode according to claim 1 or 2, characterized in that: The preparation method of the modified nanocellulose comprises: mixing cellulose, TEMPO, sodium bromide and water, adjusting the pH to 9.8-10.2, adding sodium hypochlorite, and performing an oxidation reaction at room temperature and an ultrasonic frequency of 100-150 kHz, and washing and filtering after the reaction to obtain the modified nanocellulose.
4. The method for preparing a thick electrode according to any one of claims 1 to 3, characterized in that: In the mixed slurry, the amount of the modified nanocellulose is 1.1wt%~1.5wt%.
5. The method for preparing a thick electrode according to any one of claims 1 to 4, characterized in that: The mixed slurry includes the following components in parts by weight: 1.1-1.5 parts of the modified nanocellulose; Conductive agent 0.5~1 part; 52.5-58.4 parts of electrode active material; 40~45 parts of solvent.
6. The method for preparing a thick electrode according to any one of claims 1 to 5, characterized in that: The conductive agent includes one or more of carbon black, acetylene black, carbon nanotubes, and graphene; And / or, the electrode active material includes a sodium electroactive substance or a lithium electroactive substance, the sodium electroactive substance includes one or more of sodium vanadium phosphate, sodium vanadium manganese phosphate, sodium vanadium iron phosphate, sodium iron phosphate, sodium fluorophosphate, Prussian blue analogs, sodium cobaltate, sodium manganate, sodium nickelate and sodium ferrate; the lithium electroactive substance includes one or more of lithium iron phosphate, lithium manganese iron phosphate, lithium cobaltate, lithium nickelate and lithium manganate; And / or, the solvent comprises water.
7. The method for preparing a thick electrode according to any one of claims 1 to 6, characterized in that: The freeze-drying conditions include: first freezing the mixed slurry at -70 to -30 degrees Celsius for 24 to 30 hours, and then freeze-drying at -70 to -50 degrees Celsius and 1.6 to 2.0 Pa for 24 to 48 hours.
8. A thick electrode, characterized in that It is prepared by the preparation method according to any one of claims 1 to 7.
9. The thick electrode according to claim 8, characterized in that The porosity of the thick electrode is 40% to 45%.
10. A battery, characterized in that: It comprises the thick electrode according to claim 8 or 9.
Citation Information
Patent Citations
Positive pole piece, preparation method thereof and lithium ion battery
CN117894916A